2015
DOI: 10.1063/1.4919071
|View full text |Cite
|
Sign up to set email alerts
|

Surface modification of multilayer graphene using Ga ion irradiation

Abstract: Articles you may be interested inStructural properties and dielectric function of graphene grown by high-temperature sublimation on 4H-SiC(000-1) J. Appl. Phys. 117, 085701 (2015); 10.1063/1.4908216Investigation of the effect of low energy ion beam irradiation on mono-layer graphene AIP Advances 3, 072120 (2013) The effect of Ga ion irradiation intensity on the surface of multilayer graphene was examined. Using Raman spectroscopy, we determined that the irradiation caused defects in the crystal structure of gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 40 publications
0
9
2
Order By: Relevance
“…These traps result in an increase of the apparent SP that the KPFM tries to balance by increasing the DC potential applied to the tip. This interpretation is contrary to the previous report by Wang et al who attributed the changes in SP observed in ion irradiated multilayer graphene to doping. Similarly, the doping hypothesis was also shown for the case of single graphene exfoliated on SiC .…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…These traps result in an increase of the apparent SP that the KPFM tries to balance by increasing the DC potential applied to the tip. This interpretation is contrary to the previous report by Wang et al who attributed the changes in SP observed in ion irradiated multilayer graphene to doping. Similarly, the doping hypothesis was also shown for the case of single graphene exfoliated on SiC .…”
Section: Resultscontrasting
confidence: 99%
“…The difference in topographical changes, as well as the surface potential as a function of ion dose, are shown in Figure . Low ion dose can result in ion implantation giving way to swelling of the sample's surface as shown for the case of graphene . However, in our case, contrary to that report, we cannot attribute the topographical increase to hydrocarbon layers formed on the ion‐irradiated samples.…”
Section: Resultscontrasting
confidence: 82%
See 1 more Smart Citation
“…In addition, Wang et al . studied the effects of surface modification of graphene induced by Ga + ion beam irradiation with varying dwell times and got many meaningful results 19 . Despite the fact that there are numerous achievements and research on ion modification, the majority of the materials modified by ion beam have been focused on the graphene, and the investigate of FePS 3 are rare.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental and theoretical studies showed an array of nanodots and nanowires on graphene on SiO 2 using 30 keV Ga ion irradiation [6]. The structural modification in mechanically exfoliated multilayer graphene on SiO 2 substrate caused an increase in defects with the increase in dwell time of ion irradiation, along with an increase in the compressive strain using focused ion beam (FIB) with Ga ions [7]. It was also shown that multilayered graphene is p-type doped due to defects thereby resulting in increasing the work function [7].…”
Section: Introductionmentioning
confidence: 99%